SPRINT Revisited: Updated Results and Implications. Issue 6 (11th November 2021) - Wright, Jackson T.; Whelton, Paul K.; Johnson, Karen C.; Snyder, Joni K.; Reboussin, David M.; Cushman, William C.; Williamson, Jeff D.; Pajewski, Nicholas M.; Cheung, Alfred K.; Lewis, Cora E.; Oparil, Suzanne; Rocco, Michael V.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : The SPRINT (Systolic Blood Pressure Intervention Trial) results have influenced clinical practice but have also generated discussion regarding the validity, generalizability, and importance of the findings. Following the SPRINT primary results manuscript in 2015, additional results and analyses of the data have addressed these concerns. The primary objective of this article is to respond to key questions that have been raised.